Monitoring Edentulism in Older New Zealand Adults over Two Decades: A Review and Commentary - William Murray Thomson (Hindawi Limited, 2012)
Historically, New Zealand has had the highest rates of edentulism in the world, but that rate has been falling quickly in recent decades. In 1997, projections were made for edentulism prevalence among 65-74-year-olds using national survey data from 1976 (where it was 72.3%) to 1988 (58.6%). That process assumed a logistic decline in edentulism, given that it would never have been 100% and will never get to 0%. This paper examines the validity of the projections using the estimate (29.6%) from the third national oral health survey, conducted in 2009 and considers the implications of this fall.